Impurity elements in sulfides from andesites and dacites of Upper Yurassic volcanics groups (archipelago Argentine Islands, West Antarctica) - G.V. Artemenko; V. G. Bahmutov; I. A. Samborska; L.V. Kanunnikova (Ukrainian Antarctic Journal, 2016)
As a result, of petrological, mineralogical and microprobe studies was found, that sulfide mineralization in andesites and dacites of Upper Yurassic volcanic group, investigated in Irizar, Skua and Winter Island, is synchronous and refers to the inclusions type. In dacites breccias of Irizar Islands sulphide content reaches 20—25 % of the rock. In pyrite from dacites breccia from Irizar Island present Au (0,08 %), Ag (0,04 %), Co (0,17 %) and Cu (0,12 %). In pyrites from dacites in Skua Island present Au (0,06 %) and Co (0,11 %), and in andesites from Winter Island discovered Au (0,18 %), Ag (0,05 %) and Co (0,10 %). As a result of studies found promising research of andesites and dacites of Upper Yurassic volcanic group on noble metal mineralization.